CNT-based electro-responsive shape memory functionalized 3D printed nanocomposites for liquid sensors. (December 2019) - Wan, Xue; Zhang, Fenghua; Liu, Yanju; Leng, Jinsong
Abstract: 3D printing of conductive polymer nanocomposites, which combines the electrical conductivity of nanofillers with customer-designed geometries, is promising for various sensors. However, the single shape of sensors restricts their environmental adaptability if the detecting environment changes. Herein, 3D and 4D printing of poly (D, L-lactide-co-trimethylene carbonate) (PLMC)/CNT nanocomposites with electro-responsive shape-changing capability was achieved by direct ink writing (DIW). The rheological and solvent evaporation capabilities of PLMC/CNT ink were modulated to make it printable. Electrical, mechanical, thermal and shape memory properties were investigated and various structures from micro to macro were constructed. The printed structure showed excellent shape-changing behavior under 25 V within 16 s. Then UV photoinitiators were introduced to trigger hydrogen abstraction reaction to make PLMC chains form cross-linking networks. The modified composite ink was printed into shape-changing liquid sensors. The influence of three solvents and layer thickness on liquid sensitivity was compared. The shape-changing capability helped the sensor maintain a high precision for liquid detection. The sensor in its original, deformed and recovered shape showed similar changing trend of resistance and exhibited excellent repeatability. We envision wide environmental adaptability of using the shape-changing sensor for detecting leakage of various solvents in varying environment. Graphical abstract: Image 1